Analisis dan Penerapan Manfaat Kandungan Senyawa Daun Miana (Coleus scutellarioides (L.) Benth.) di Kiaracondong Kota Bandung - Najmi Azalia Ubaedilah; Ateng Supriyatna (PPPM POLITEKNIK NEGERI SAMBAS, 2023)
Miana plants (Coleus scutellarioides (L.) Benth.) are ornamental plants with physical characteristics of leaves that have a variety of colors and are abundant in nature. The purpose of this service is to analyze the content of miana leaves, apply the benefits of miana leaves for the community, and collect data and information from various literary sources as a reference for the community regarding the various benefits of miana leaves so that the public knows about them. The method used is preparation by conducting literature studies, collecting and analyzing data from several writings that discuss the benefits of miana leaves which are reviewed based on their phytochemical substances and pharmacological activities as well as providing information to the public, and direct assistance to the community. Based on the results of the analysis, miana leaves contain several compounds which include anthocyanins and compounds that have pharmacological activity as antimicrobials such as flavonoids, essential oils, saponins, and many other compounds. The dedication that has been carried out shows that the assistance has been successful, seeing that miana leaves are a solution for the community, including being used as a natural dye in the food sector, an additive in cosmetic products, as well as being a medicine for more than one disease.